Function and regulation of transcription factors involved in root apical meristem and stem cell maintenance - Drisch, Rebecca C.; Stahl, Yvonne (Frontiers in Plant Science, 2015)
Plant roots are essential for overall plant development, growth and performance by providing anchorage in the soil and uptake of nutrients and water. The primary root of higher plants derives from a group of pluripotent, mitotically active stem cells residing in the root apical meristem (RAM) which provides the basis for growth, development and regeneration of the root. The stem cells in the Arabidopsis thaliana RAM are surrounding the quiescent center (QC), which consists of a group of rarely dividing cells. The QC maintains the stem cells in a non-cell-autonomous manner and prevents them from differentiation. The necessary dynamic but also tight regulation of the transition from stem cell fate to differentiation most likely requires complex regulatory mechanisms to integrate external and internal cues. Transcription factors play a central role in root development and are regulated by phytohormones, small signaling molecules and miRNAs. In this review we give a comprehensive overview about the function and regulation of specific transcription factors controlling stem cell fate and root apical meristem maintenance and discuss the possibility of TF complex formation, subcellular translocations and cell-to-cell movement functioning as another level of regulation.